ANALISIS KEBUTUHAN RAK DOKUMEN REKAM MEDIS DI RUMAH SAKIT - Istiyawati Rahayu; Intan Oktaviani (Jurnal Infokes, 2023)
The hospital is one of the main destinations for people to do treatment. The large number of patients who visit a hospital makes the accumulation of RM data. The importance of RM data management in a hospital greatly affects the level of service to patients. Disorganization in managing RM documents is one of the problem factors faced by hospitals, this information is obtained from the results of observations in storing and managing medical record data. The layout of the medical record data storage area and the size of the unsupported filing area are also factors causing the problem. The purpose of conducting research is to produce a model for storing and managing RM data according to the needs of the hospital. A retrospective approach is used in this descriptive research model. The data collection model uses observation and question and answer. Data processing is done by collecting data, processing data, tabulating, presenting data. The results of the data that has been processed then carried out an analysis with a descriptive approach. Calculating the need for shelves to store medical record data as needed with the roll o' pack rack model is the result of the research that has been done. Supporting medical record data storage rooms are also needed to support the ease of managing medical record data. The use of the roll o'pack rack model is recommended to store and manage RM documents in a neater and more efficient place.